2017
DOI: 10.19082/5388
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices toward prevention of hepatitis B virus infection among medical students at Northern Border University, Arar, Kingdom of Saudi Arabia

Abstract: Background and aimHealth care workers’ risk of occupational exposure to HBV is a chief concern, particularly with young students in the health profession.This study was carried out to assess the knowledge regarding symptoms, risk factors and prevention of hepatitis B virus infection among medical students.MethodsA cross-sectional study was carried out from November 01, 2016 to May 30, 2017 on medical students at the Northern Border University (Arar, Kingdom of Saudi Arabia). Data were collected from 200 studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
23
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 23 publications
14
23
6
1
Order By: Relevance
“…Similar results are also reported by a study at the Faculty of Medicine in Foča (B&H), where 93.5% of them consider vaccination as the most important measure for the prevention of hepatitis B [13]. Likewise, some other studies show similar results [17][18][19][20]. Attitudes of the students on HBV positive patients were estimated based on 10 claims set and 5 offered responses of intensities reflecting a higher or lower degree of agreement with a particular statement.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar results are also reported by a study at the Faculty of Medicine in Foča (B&H), where 93.5% of them consider vaccination as the most important measure for the prevention of hepatitis B [13]. Likewise, some other studies show similar results [17][18][19][20]. Attitudes of the students on HBV positive patients were estimated based on 10 claims set and 5 offered responses of intensities reflecting a higher or lower degree of agreement with a particular statement.…”
Section: Discussionsupporting
confidence: 75%
“…We must also consider the fact that the respondents are students of the first two grades of faculty and that there is still plenty of space to improve their level of knowledge on this important topic. In most similar studies on this topic, there was a lack of student knowledge of most aspects of HBV infection [14][15][16][17][18], while on the other hand there are studies where the level of knowledge was assessed positively [19][20]. Based on the question of our current experience of blood and sexually transmitted diseases, most of them have come into direct contact with the blood of another person, while most of them have never been tested on blood and sexually transmitted diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the attitudes of medical students at Tanta University, Egypt, toward hepatitis B and C revealed that only 57.8% of participants had sufficient knowledge; 63.3% had incorrect knowledge of modes of transmission of infection, 49.7% did not know that there is a treatment for B and C viral hepatitis, and 13.5% did not know that there is a vaccine for B viral hepatitis [21]. In contrast, a study in northwest Ethiopia [22], and a study at Northern Border University, Saudi Arabia, [18] showed that medical students had good knowledge of the mode of transmission and prevention of HBV, findings inconsistent with those of the present study. In addition, a study of medical students in Hail, Saudi Arabia, demonstrated that most participants had adequate knowledge of HBV infection and its mode of transmission, 73.6% knew that HBV infection was associated with liver cancer, and 81.4% were aware of the HBV vaccine and that it provides protection against HBV infection [23].…”
Section: Discussionmentioning
confidence: 99%
“…Zaštitne mjere protiv profesionalnih virusnih infekcija kod stomatoloških radnika su obavezne. Mnoge studije bavile su se ispitivanjem znanja stomatologa i studenata stomatologije o prenošenju virusnih infekcija u stomatološkoj ordinaciji [44][45][46][47][48][49]. Većina ispitanika je upoznata sa putevima transmisije i načinima zaštite.…”
Section: Sprovođenje Mjera Zaštite Od Virusnih Infekcija U Stomatološunclassified